An Analysis of Tax Avoidance in Food Beverage Companies Registered in Indonesia Stock Exchange - Dwi Dewianawati; Erry Setiawan (Publisher Cv. Inara, 2021)
The increasing growth in the food and beverage company indicates the high profitability of the company. Profitability describes the condition in which a company can generate profits at a certain level of sales, assets, and share capital. An increase in profitability requires companies to pay high taxes as well, but in reality, taxpayers do not comply with the tax obligations through tax avoidance attempts. This study aims to determine the effects of profitability and leverage simultaneously on tax avoidance. It is to assess the impact of profitability and leverage partially on tax avoidance. The population used in this study was a food and beverage company registered in the Indonesia Stock Exchange (IDX) during 2017-2019. Furthermore, this study utilized a purposive sampling technique as its sampling technique with a sample size of 13 companies. Multiple Regression Model was employed to determine the effect of independent variables on the dependent variable. Based on the study results, it could be concluded that the variables of Return on Assets (ROA) and leverage simultaneously related to tax avoidance practices in food and beverage companies registered in the Indonesia Stock Exchange (IDX). The variable of Return on Asset (ROA) ratio did not significantly affect tax avoidance in food and beverage companies in the Indonesia Stock Exchange. Meanwhile, leverage significantly affected tax avoidance in food and beverage companies in the Indonesia Stock Exchange. The leverage variable had a dominance effect on tax avoidance in food and beverage companies in the Indonesia Stock Exchange.